1997
DOI: 10.1016/s0378-4371(96)00480-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical scaling behavior of the Swift-Hohenberg equation following a quench to the modulated state

Abstract: We study the kinetics of phase transitions in a Rayleigh-Benard system after onset of convection using 2D Swift-Hohenberg equation. An initially uniform state evolves to one whose ground state is spatially periodic. We confirmed previous results which showed that dynamical scaling occurs at medium quench (ǫ = 0.25) with scaling exponents 1/5 and 1/4 under zero noise and finite noise respectively. We find logarithmic scaling behavior for a deep quench (ǫ = 0.75) at zero noise. A simple method is devised to meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
68
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 11 publications
(16 reference statements)
10
68
1
Order By: Relevance
“…Such a description, valid for distances much larger than the defect core, typically involves time dependent Ginzburg-Landau equations or their generalizations. A few cases have been studied extensively, including domain coarsening in O(N) models [3,4], in nematics [5][6][7][8], and in smectic phases as effectively encountered in models of Rayleigh-Bénard convection or lamellar phases of block copolymers [9][10][11][12][13][14][15]. In the case of modulated phases, the motion of a single defect has been widely studied within the well known amplitude equation formalism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a description, valid for distances much larger than the defect core, typically involves time dependent Ginzburg-Landau equations or their generalizations. A few cases have been studied extensively, including domain coarsening in O(N) models [3,4], in nematics [5][6][7][8], and in smectic phases as effectively encountered in models of Rayleigh-Bénard convection or lamellar phases of block copolymers [9][10][11][12][13][14][15]. In the case of modulated phases, the motion of a single defect has been widely studied within the well known amplitude equation formalism.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Sections II and III provide a possible interpretation of conflicting results in the literature. Previous studies of this problem [10][11][12][13][14][15] addressed the existence of self-similarity during domain coarsening and attempted to quantify the time dependence of the linear scale of the coarsening structure. The statistical self-similarity hypothesis asserts that after a possible transient, consecutive configurations of the coarsening structure are geometrically similar in a statistical sense.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a wide variety of scaling exponents may be observed [21] which is dependent on a parameter describing the depth of the quench which leads to crystallization. Dynamic scaling of pattern domains has also been studied in the context of convection patterns [24][25][26][27]. Scaling exponents in these studies range from 1/5 to 1/3, depending on how far the system was from onset of instability and whether noise was included.…”
mentioning
confidence: 99%
“…A canonical measure for this length is the width of the structure factor [7,8,9,10,11,12]: in a defect-free domain the order parameter field takes the form φ(x, t) ≃ A(x, t) cos(q(x, t) · x)+higher harmonics (7) where A(x, t) and q(x, t) vary slowly within the domain. Thus, in the absence of any defects one expects the structure factor S(q, t) = |φ q (t)| 2 of an infinite system to be a delta function centered around q = q 0 .…”
mentioning
confidence: 99%
“…Similar to other models, in which this coarsening process is self-similar [6], any linear scale of the structure is expected to grow as a power law in time ξ ∼ t 1/z . However, simulations of sudden quenches of the SH equation [7,8,9,10,11,12] have revealed that the observed exponent z is sensitive to non-universal model features such as the quench depth or noise strength. Moreover, different definitions of the length scale have led to different exponents with values reported in the interval 2 ≤ z ≤ 5.…”
mentioning
confidence: 99%